A global/local approach based on CUF for the accurate and efficient analysis of metallic and composite structures. (1st June 2019) - Carrera, E.; Fiordilino, G.A.; Nagaraj, M.; Pagani, A.; Montemurro, M.
Highlights: A novel global/local finite element approach is developed. The method makes use of the Carrera unified formulation to enhance the solution in critical areas. Global analyses are performed with available finite element tools, such as Nastran and Abaqus. By using higher-order models in critical areas, it is possible to recover accurate stress/strain fields. The method is demonstrated to be very effective for both metallic and composite structures. Abstract: The design and analysis of aerospace structures requires a detailed evaluation of stresses. Nevertheless, the complexity of large structures and the use of composite materials can significantly increase the computational costs of the models. The computational burden of such analyses can be reduced by a suitable global/local approach developed in a very general Finite Element framework. Generally, a global/local modelling approach aims at using a finer mesh in the "local" zones where a detailed evaluation of stress/strain field is required, whereas a coarse mesh is used in the rest of the structure. This work proposes a global/local methodology to set up a high-order beam model in the Carrera Unified Formulation framework only for a reduced region of the global model. The methodology makes use of two steps. In the first step, a static analysis of the global structure is done by means of a commercial software in order to identify the critical regions deserving more accurate investigations. In the second step, thus, a high-order beam model is employed for the local region based on the information from the previous global analysis. Linear elastic static analysis are considered in this work, and the attention is mainly focussed on the capability of the method to provide stable solutions and accurate 3D stress fields in the local region, even in the case of laminated composite structures. Hence, the effectiveness of the proposed approach is proven through some meaningful benchmarks.